Farmer Household Income Exchange Rate in Bingin Kuning District, Lebong Regency, Bengkulu - Panriski, Nesi; Mulyasari, Gita; Yuliarti, Ellys; Trisusilo, Agung; Sriyoto, Sriyoto (Badan Penerbitan Fakultas Pertanian (BPFP), 2024)
The Farmer Household Income Exchange Rate (NTPRP) is used to determine the level of welfare of farmer households. This research aims to analyze the income structure of rice farmer households in Bingin Kuning District, Lebong Regency, analyze the consumption expenditure patterns of rice farmer households in Bingin Kuning District, Lebong Regency, and analyze the rice farmer household income exchange rate (NTPRP) in Bingin Kuning District, Regency. Lebong. The research was conducted in Bingin Kuning District, Lebong Regency. The population in this study was rice farmers. The sample for this research was 94 farmers using Simple Random Sampling. The analytical method used in this research is descriptive quantitative. Quantitative descriptive analysis helps to understand the income structure, consumption expenditure patterns, and the farmer household income exchange rate (NTPRP). The study results show that the welfare of rice farmer households in Bingin Kuning District, Lebong Regency, is not prosperous.